Empowering Muslim Women Though Executive Coaching & Mentoring - Fadila Grine (UIN Sunan Gunung Djati Bandung, 2014)
This paper examines the role and effect of executive coaching and mentoring on the empowerment of Muslim women and enhancing their levels of contribution. It further substantiates the manner in which executive coaching can accommodate both the nature and needs of Muslim women while further unleashing her respective talents, creativity and skills. The study further highlights the role and significance of coaching in spheres relevant to family, as well as social and career development. This study highlights the use of the strategic technique for personal and leadership development set to explore talents, leaders and implicit abilities. Moreover, it exhibits the flexibility of self-coaching and its appropriateness for Muslim women, especially concerning self-development, which in turn influences social and institutional development. This inquiry highlights a number of practical results which emphasizes the viability and efficacy of executive coaching on personal and institutional levels as far as the making of better world for Muslim women is concerned.